On Ideals and Homology in Additive Categories - Lucian M. Ionescu (International Journal of Mathematics and Mathematical Sciences)
Ideals are used to define homological functors in additive categories. In abelian categories the ideals corresponding to the usual universal objects are principal, and the construction reduces, in a choice dependent way, to homology groups. The applications considered in this paper are: derived categories and functors.